ألعاب البحر الأبيض المتوسط بوهران وأثرها على الصورة السياحية الداخلية للجزائر - دراسة تحليلية لآراء عينة من متابعي ألعاب البحر الأبيض المتوسط بوهران- - بوشلخة زينب; طبايبية سليمة (جامعة الوادي University of Eloued, 2024)
This study aims to assess the influence of embracing and hosting sports events on the perception of domestic tourism in Algeria. To achieve this, a field study was conducted on a group of followers of the Mediterranean Games in Oran. A survey was distributed to gather feedback from both attendees and viewers of the Mediterranean Games in Oran, utilizing the statistical software package (SPSS version25). The key recommendations of the study include: • Working to organize and host a wide range of sports events and exhibitions. • Promoting sporting events and activities through various channels. • Emphasizing the importance of collaboration between the sports and tourism sectors
The Oran Mediterranean Games and their impact on Algeria’s domestic tourism image -An analytical study of the opinions of a sample of supporters of the Oran Mediterranean Games -
Keywords: السياحة الداخلية; الصورة السياحية; التظاهرات الرياضية; ألعاب البحر الأبيض المتوسط; Domestic tourism; tourist image; sports events